Specifics of combating corruption at higher education institutions in the context of integrity policy - O. S. Bondarenko (Law and Safety)
The article is devoted to the criminological characteristics of the specifics of combating corruption at higher education institutions in the context of the integrity policy. At the same time, the right to education is a fundamental right, therefore the State is not obliged to ensure the right to higher education for all citizens. Despite this, the majority of Ukrainian citizens have one or even several higher education degrees. Given the popularity of educational services, they are inevitably associated with various corruption risks: from the process of enrolment to a higher education institution and ending with obtaining an educational degree at all levels.